The Effects of Progressive Muscle Relaxation on the Level of Anxiety in Nurses Caring for Patients with Covid-19 - Yolanda, Yori; Said, Irfan; Suryati, Tati; Simanungkalit, Ria (Indonesian Contemporary Nursing Journal (ICON Journal), 2022)
Introduction: One of the psychological responses encountered by nurses who treat COVID-19 patients is anxiety. The anxiety is caused by several factors including feelings of unsupported, worrying excessively about health, fear of carrying the infection and transmitting it to family members or others, a heavy workload, social stigmatization, feeling insecure for providing care. Moreover, this psychological problem caused low quality of health services for patients. Therefore, to reduce the anxiety of nurses who took care for Covid-19 patients, anxiety management using progressive muscle relaxation was needed. The purpose of this study is to assess the effect of progressive muscle relaxation on the level of anxiety in nurses caring for patients with Covid-19. Method: The research design used in this study was quasi-experimental, namely pre-test and post-test with control group design with purposive sampling technique. The number of samples is 52 nurses. The research instrument used the Zung Self-Rating Anxiety Scale (SRAS) questionnaire. The paired T Test is applied for statistical analysis. Result: the result of this study indicated that progressive muscle relaxation had a substantial effect on the level anxiety in nurses caring for patients with Covid-19 in the intervention group with a P-value 0.000 (P value < 0,005). Conclusion: Progressive muscle relaxation therapy is a complementary therapy that can be done independently by nurses and is effective in reducing anxiety.